2017
DOI: 10.31223/osf.io/gxh3f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of cutoff-related knickpoints during early evolution of submarine channels

Abstract: Submarine channels are often thought of as having relatively simple geometries, with significant alongchannel morphologic and stratigraphic continuity. Using high-resolution seismic reflection data from offshore Angola and a kinematic model of channel evolution, we present evidence that channels on the seafloor can develop slope variability as a result of meander cutoff events. When cutoffs develop, the shortened flow paths produce locally steep gradients, thus initiating knickpoints. Waves of knickpoint retre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Commonly, channel architecture records a protracted history of incision and deposition at multiple scales related to different types of sediment‐gravity flows (Hubbard et al ., ). The main features of the sediment‐gravity flows, such as magnitude and both density and type of transported sediment, may vary as a consequence of changes in allogenic (for example, tectonics and sea‐level fluctuations) and autogenic (for example, channel avulsions) factors (Pirmez et al ., ; Kneller, ; Jobe et al ., ; Sylvester & Covault, ).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, channel architecture records a protracted history of incision and deposition at multiple scales related to different types of sediment‐gravity flows (Hubbard et al ., ). The main features of the sediment‐gravity flows, such as magnitude and both density and type of transported sediment, may vary as a consequence of changes in allogenic (for example, tectonics and sea‐level fluctuations) and autogenic (for example, channel avulsions) factors (Pirmez et al ., ; Kneller, ; Jobe et al ., ; Sylvester & Covault, ).…”
Section: Introductionmentioning
confidence: 99%
“…Astoria Canyon, Oregon; San Antonia Canyon, Chile; Monterey Canyon, California; Scripts Canyon, California; Mitchell, , ); on open continental slopes (New Jersey continental slope; Mitchell, ); as deep‐water ‘waterfalls’ (Monterey Fan; Masson et al, ); within headless channels (Lake Geneva; Girardclos et al, ); in lakes (Lake Geneva; Lake Wabush; Girardclos et al, ; Turmel et al, ); and in channel meander bed cut‐offs (e.g. offshore Angola; Sylvester and Covault, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, system morphology strongly influences the shape and location of valuable oil and gas reservoirs. This affects the shape and distribution of sand layers deposited by submarine channels, or in delta lobes (Weimer and Pettingill, ; Sylvester and Covault, ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstorder questions remain concerning how submarine knickpoints migrate upstream, and how knickpoint migration interacts with smallerscale associated crescentic bedforms, influencing the longer-term submarine channel evolution and the resulting sedimentary record. Although the morphology and formation mechanisms might differ, knickpoints are observed globally in various settings, and have been reported from erosional submarine canyons (for example, San Antonia Canyon, offshore Chile; Mitchell, 2006), open continental slopes (New Jersey continental slope; Mitchell, 2006), deep-water 'waterfalls' (Monterey Fan; Masson et al, 1995), headless channels (Girardclos et al, 2012) and submarine channel meander bend cut-offs (Cantelli & Muto, 2014;Sylvester & Covault, 2016). In a previous study of Bute Inlet, Heijnen et al (2020) showed that submarine knickpoints can dominate submarine channel and channel-bend evolution, and can migrate upstream very rapidly (hundreds of metres per year).…”
Section: Introductionmentioning
confidence: 99%